(3JCKjQ GdebGQHI GdeYQajI Ydi eMJhi GdcJGH GdeOQSj hOhQg aj GdYedjI GdJYdejIs - (3fMGS, LhQLs ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2007)
(3jTjQ GdHMK Edi Cf GdcJGH GdeOQSj hSjdI JYqdeqjI gGqeI(B. (3hgh jTqcd, MJi Gdjhe, aj GdfXGe GdJQHhj GdYQHj YehekG, QcjRI CSGSqjI ef GdQcGFR GdJYdjeqjI(B. (3jbhe GdJYGWj eY GdcJGH GdeOQSj Ydi Cfg hSjdI ddJYqde(B. (3dcf, jecf dgPg GdhSjdI Cf JJMqhd Edi ebqheI SdHjI aj ZjGH eYGjjQ hGVMI JMce eMJhGgG hENQGLgG hWQjbI GSJYeGdgG(B. (3jecf ddebGQHI GdeYQajI GdbGFeI Ydi GdfeGFqjI ef LgI, hYdi GdHfGFqjI ef LgI CNQi, Cf JTqcd GdNdajI GdefGSHI dJCejf(B: (3hMOI fgGLqjI Hjf eNJda GdcJH GdeOQSqjI, hGMJQGe feGA GdeJYqde heTGQcJg aj GdYedqjI GdJYqdeqjI HTcd eJhGmR, hJMUjf OhQ GdeYqde cejqSQ ddYedqjI GdJCgjdqjI(B. (3HGdGYJeGO Ydi gPg GdebGQHI jecf hVY eYGjjQ JUdM ceQLYqjI aj Jbjje GdcJGH GdeOQSj haqYGdjJg(B. (3hjSJYQV GdHMK dETcGdjI GdebGQHI GdeYQajI ddcJGH GdeOQSj hgOagG, ceG jYQV ddaQVqjI GdJj jSYi Edi HQgGfgG GfWdGkbG ef aQVjGJ YedGfjI eMnqOOI(B. (3hGfWdGkbG ef JMdjd dhGbY HYV SdGSd GdcJH GdehLhOI(B. (3CNjQkG jbJQM GdHGMK HYV GdeYGjjQ GdJj jecf Cf JTcd bGYOI dOQGSI GdcJH GdeOQSjI efgLkjG ef CLd JbjjegG, ceG jXgQ UdGMqjI gPg GdeYGjjQ dOQGSI GdcJH GdeOQSqjI GdeJOGhdI hJbjjegG(B.s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Approche cognitive; Cognitive Approach; Livres Scolaires; Textbooks; (3GdcJGH GdeOQSjs; (3GdebGQHI GdeYQajIs